Warehousing Process Flow Analysis Using Lean Warehousing Approach For Waste Minimization At PT XYZ - Salma Putria Nabila; Sumiati Sumiati (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
This research aims to identify and minimize waste in the warehousing process at PT XYZ using the lean warehousing approach. The problems faced are non-value added activities such as waiting time, repetitive movements, and inappropriate material placement. The methods used include observation, interviews, data collection, and analysis using Value Stream Mapping (VSM) and Process Activity Mapping (PAM). The results showed five main wastes, namely waiting time, defects, unnecessary motion, and excess inventory with the highest weights of 3.75 to 3.25. Implementation of improvements reduced six NVA activities, decreased the number of activities from 31 to 25, and saved activity time from 338 minutes to 243 minutes. In addition, Process Cycle Efficiency (PCE) increased by 25.36% from 46.74% to 72.1%. This research is expected to improve warehouse operational efficiency and become a reference for the application of lean warehousing in the electricity sector.